Leptospirosis: An important re-emerging infection of animals and man - BISIAS (Γ. ΜΠΙΣΙΑΣ) G.; KRITAS (Σ.Κ. ΚΡΗΤΑΣ) S. K.; BURRIEL, A.; KONTOS (Β. ΚΟΝΤΟΣ) B. (Journal of the Hellenic Veterinary Medical Society, 2017)
Leptospirosis, a re-emerging infection of animals and man, is caused by one of 200 serotypes of Leptospira spp. The genus is currently divided into eight pathogenic species, infecting various animal species and man, either clinically or subclinically. Natural hosts of the microorganism are traditionally, but not exclusively, considered to be rodents. Infected animals excrete Leptospira in the environment, where it may remain for long periods of time, especially if temperatures are about 25°C. The reportedprevalence of infected animals from around the world is between 2% and 46%. In Greece, recent reports show a seropositivity among abortion cases of small ruminants around 25%, while the relevant percentage among apparently healthy food producing animals is between 5.7% and 16.2%. The most prevalent serotypes were Bratislava, Australis and Copenhageni, depending on the animal species. There is a need for more systematic study of the infection in Greece (especially with the possibility of the expected climatic changes to result in a temperature rise).